2017
DOI: 10.1016/j.pneurobio.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Brain-immune interactions in perinatal hypoxic-ischemic brain injury

Abstract: Perinatal hypoxia-ischemia remains the primary cause of acute neonatal brain injury, leading to a high mortality rate and long-term neurological deficits, such as behavioral, social, attentional, cognitive and functional motor deficits. An ever-increasing body of evidence shows that the immune response to acute cerebral hypoxia-ischemia is a major contributor to the pathophysiology of neonatal brain injury. Hypoxia-ischemia provokes an intravascular inflammatory cascade that is further augmented by the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
189
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(203 citation statements)
references
References 252 publications
(296 reference statements)
6
189
0
1
Order By: Relevance
“…Increasing evidence suggests that post‐ischemic inflammation plays an important role in evolution of brain damages after ischemia (Ziemka‐Nalecz et al, 2017). Hours after onset of cerebral ischemia, a cascade of inflammatory events is initiated through activation of resident cells, among which activated microglia released inflammatory cytokines and increased neuronal death (Li et al, 2017). Our results displayed microglia activation after neonatal HI, and showed that NLRP3 expressed mainly in microglia rather than astrocyte.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing evidence suggests that post‐ischemic inflammation plays an important role in evolution of brain damages after ischemia (Ziemka‐Nalecz et al, 2017). Hours after onset of cerebral ischemia, a cascade of inflammatory events is initiated through activation of resident cells, among which activated microglia released inflammatory cytokines and increased neuronal death (Li et al, 2017). Our results displayed microglia activation after neonatal HI, and showed that NLRP3 expressed mainly in microglia rather than astrocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia is a major source of NLRP3 activation and can produce IL‐1β in response to different classical inflammasome activators, such as such as ATP and nigericin. In HIE of human infants, microglial activation and aggregation are the pathological markers(Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, age impacts on brain functioning, once it was observed in a previous study that the same neonatal anoxia model, at PND 90, decreased the %OAT and the percentage of time spent on the closed arm was significantly higher in adult male subjected to neonatal anoxia than in control animals Which altered cellular mechanisms would be responsible for these damages? Accumulated evidence has acknowledged the following events: neuronal apoptosis, reactive gliosis, oxidative stress, excitotoxicity, inflammation and disruption of blood-brain barrier as linked to the neonatal brain damage induced by neonatal anoxia (Beilharz et al, 1995;Buwalda et al, 1995;Wei et al, 2004;Borutaite et al, 2013;Fang et al, 2017;Li et al, 2017;Li et al, 2018). Notably, sex-specificity in many of these processes occurs in normal brain development and may be a reason to male and female differentially respond to neonatal oxygen deprivation, which in turn alters their developmental program and cognitive functions, as also shown in the onset of ontogenetic reflexes and somatic development (Kumar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%